Return to competitive gymnastics training in the UK following the first COVID-19 national lockdown - Patel, T. S.; McGregor, A.; Cumming, S. P.; Williams, K.; Williams, S. (Scandinavian Journal of Medicine & Science in Sports, 2022)
Following the outbreak of COVID-19 (coronavirus), the UK entered a national lockdown, and all sport was suspended. The study aimed to explore the process of returning to gymnastics training after several months away from the gym, with a particular interest towards training load and injury. Twenty-six, national programmed gymnasts from Men's artistic, Women's artistic and Trampoline gymnastics recorded training load and injury whilst returning to training. At the end of data collection, three coaches were interviewed to further explore the experiences and practices of returning to training. Home-based training during lockdown was seen as beneficial in maintaining a level of fitness. Coaches described a gradual increase in training to reduce the risk of injury, and this partly explains a non-significant association between training load and a substantial injury (p = 0.441). However, week-to-week changes in training load following periods of additional restrictions (additional lockdown, periods of isolation, or substantial restrictions) were not always gradual. There was a significant association between an injury in the preceding week (niggle or substantial injury to a different body part) and a substantial injury in the subsequent week (RR: 5.29, p = 0.011). Monitoring training was described to be a useful practice during the process of returning to training. Coaches believed that although the short-term development of their gymnasts was affected, the long-term development would not be impacted from COVID-19. It is anticipated that learnings from this study can be applied to future practices and situations, particularly when gymnasts are away from the gym for an extended period.